2011
DOI: 10.3892/etm.2011.430
|View full text |Cite
|
Sign up to set email alerts
|

Glycan-related gene expression signatures in human metastatic hepatocellular carcinoma cells

Abstract: Abstract. Human hepatocellular carcinoma (HCC) ranks second in cancer mortality in China; recurrence and metastasis have been the cause of the high mortality. Glycans on the cell surface play a pivotal role in tumor metastasis. The global alteration in the structure and composition of N-glycans during HCC metastasis remains unknown. To understand glycan alterations of glycoproteins by correlating the glycosyltransferase expression profile with glycan structure, we systematically used glycan profiling tools: gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 19 publications
(19 reference statements)
1
25
0
Order By: Relevance
“…A higher level of expression of sLe a indicates stronger tumor invasion [36]. Consistent with previous study [15], the β3GalT5 glycogene was increased in the HCC EMT model; it implied that β3GalT5 and its product may play an important role in the development and metastasis of HCC.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A higher level of expression of sLe a indicates stronger tumor invasion [36]. Consistent with previous study [15], the β3GalT5 glycogene was increased in the HCC EMT model; it implied that β3GalT5 and its product may play an important role in the development and metastasis of HCC.…”
Section: Discussionsupporting
confidence: 88%
“…It is responsible to form the glycosidic bound by adding β1, 3Gal residues to GlcNAcβ1-3Galβ1-4GlcNAcβ1-R branched and then generated sLe a structure which was bound by lectin AAL. Our previous study [15] found that β3GalT5 glycogene was up-regulated in high metastatic potential HCCLM3 cells by glycogene microarray. After knocking out β3GalT5, the ability of invasion and migration for HCCLM3 cells were decreased significantly.…”
Section: Resultsmentioning
confidence: 94%
“…Song et al reported that the bisecting GlcNAc on N -glycans inhibited growth factor signaling and retarded mammary tumor progression [32]. However, MGAT3 was reported upregulated in high metastatic human hepatocarcinoma cell line HCCLM3 in comparison with cell line with low metastatic potential [66]. Overexpression of MGAT3 in HeLaS3 cells enhanced the epidermal growth factor (EGF) mediated cell signaling [67], and transfecting myelogenous leukemia cell line K562 with MGAT3 protected it from natural killer cytotoxicity and increased spleen colonization [68].…”
Section: Discussionmentioning
confidence: 99%
“…1 It has shown that oligosaccharide expression may be associated with carcinogenesis, metastasis and development of chemoresistance of malignant cells. 2, 3, 4 Although the alterations of glycan structures are observed in drug resistance leukemia cells, 5, 6 there is limited report about the effects of GTs and corresponding glycogenes in the development of leukemia drug resistance.…”
mentioning
confidence: 99%